ФОЛЬКЛОРНЫЕ ТРАДИЦИИ В ТВОРЧЕСТВЕ ДЖАЛАЛЕДДИНА РУМИ (Journal of Oriental Studies, 2018)
Jalaladdin Rumi is a famous Turkish literature had left an unforgettable trace with his legacy that reflectsthe folk traditions of whole East. With researching his creation by direction of study of folklore wereclarified the folk traditions, the motifs of legends, tales and religious content in his works. This articleare considered the motifs of folklore creations of turks on the base of bringing examples from J.Rumi’s“Mesnevi”.